Marriage is scary trend: Narratives of fear of marriage for women - Putri, Harvina (Glocal Society Journal, 2025)
The term "marriage is scary," prevalent on social media, conveys the notion that marriage is intimidating, often through narratives that portray it negatively. This study seeks to examine the "marriage is scary" trend, particularly focusing on the phenomenon of marriage-related fear among women, by analyzing content from the TikTok platform. The research identifies the factors influencing women's perceptions of the "marriage is scary" narrative and explores how this trend has become emblematic of popular culture on social media. The investigation employs a qualitative approach, utilizing content analysis and interviews. The research setting is the TikTok platform, with a focus on content and comment sections. Informants are active TikTok users selected through purposive sampling, and the data comprises narrative analysis results and interviews with netizens regarding "marriage is scary" content. The study reveals that content analysis of the "marriage is scary" narrative highlights issues such as familial problems, fear in partner selection, marital advice, and life demands within marriage. Women's perceptions of the narrative are influenced by challenges of long-term commitment and are considered a natural phenomenon. These perceptions are shaped by factors such as social pressure, relatable content, social and cultural changes, the influence of social media, and personal experiences and trauma. The study identifies two positive aspects of the viral "marriage is scary" trend: the notion of sharing as caring and the importance of selectivity in decision-making. Conversely, the trend also has negative impacts, including the creation of a negative stigma around marriage and a decline in marriage rates.